VD_FINDINFO MP / 2022 / 7 vom 14. Dezember 2022 - VD Tribunal cantonal (2022)
LÉGITIMATION ACTIVE ET PASSIVE, INTÉRÊT DIGNE DE PROTECTION, SECRET D'AFFAIRES, CONCURRENCE DÉLOYALE | 5 let. a LCD, 5 let. b LCD, 5 let. c LCD, 6 LCD, 9 al. 1 LCD, 136 LDIP, 31 CL (2007), 264 CPC (CH), 267 CPC (CH)